ANALISIS KINERJA LEMBAGA PENYULUHAN DI KABUPATEN INDRAGIRI HULU - Mely Susanti; Rosnita Rosnita; Roza Yulida (Jurnal Ilmiah Pertanian, 2017)
The aims of this study is to describe and analyze the performance of extention institutions in Indragiri Hulu District. The study was conducted in BP4KKP Indragiri Hulu. The number of samples in this study was 127 people including 6 people from BP4KKP that was taken by using purposive sampling and this technique was also used to determine the four districts selected samples which are representative of the population of the district. Samples of farmers were 98 people which were taken by using slovin formula and 23 extention workers by using census method. Description of extension institution was taken by using descriptive analysis and analysis of extension institution was taken by Summated Likert Scale Rating (SLR). The results of this study showed that The role, functions and duties of the extension field has not been fully implemented It can be seen from there are some programs that are not running, then the background of personnel BP4KKP is not suitable with the placement of job profile. The institution has already referred to the Law No. 16 of 2006 which is polyvalent. The common perception among farmers and extention workers toward the performance of institutions was considered by four indicators, namely: responsiveness, responsibility, accountability and quality of service, they showed the results of the institution's performance was in a high category .The problem faced is the small number of extention workers and the low productivity of rice and prevalence of institutional support.